Design of Website-Based E-Commerce Information System Using Extreme Programming Method (Case Study: Belv Boutique) - Syihan Achmad; Arief Ichwani (Fakultas Teknik Universitas Lambung Mangkurat, 2025)
The purpose of this research is to provide a REST API-based web service for an online fashion product ordering platform, using butik belv as a case study. The purchase process carried out at butik belv At this time, consumers must visit butik belv directly to complete their purchase because it is currently still processed offline, where payments are still made in cash and buyers must visit the store directly to complete the purchase. Payments and transactions are still paid in cash. In addition, sales transactions are still recorded manually which are prone to errors. This research aims to create a web application that utilizes REST API technology. With the help of this application, users can order products online and pay directly through the website without having to visit the store. In addition, the transaction recording system is automated, thus ensuring that all sales data is recorded accurately, this reduces the possibility of recording errors and simplifies the sales reporting process. Extreme programming is the software development methodology used. It includes design, coding, testing, and planning phases. The system also uses Blackbox testing which is expected the test results show that each functionality works as intended, indicating that the use of web services can increase the speed of the application and streamline the purchasing process and assist buyers in the purchasing process. Butik butik belv anticipates increased operational effectiveness and provides this solution.